2006
DOI: 10.1002/chin.200640176
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,5‐Benzodiazepine Derivatives Catalyzed by Zinc Chloride.

Abstract: Multi-membered N-heterocycles R 0690 Synthesis of 1,5-Benzodiazepine Derivatives Catalyzed by Zinc Chloride. -Zinc chloride is a useful catalyst for the cyclocondensation of ketones with o-phenylenediamine. -(PASHA*, M. A.; JAYASHANKARA, V. P.; Heterocycles 68 (2006) 5, 1017-1023; Dep. Stud. Chem., Cent. Coll., Bangalore Univ., Bangalore 560 001, India; Eng.) -Mais 40-176

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…Furthermore, SiO 2 -NaHSO 4 has been used in the protection of aldehydes with 2-mercaptoethanol [18]. In a continuation of our work into the synthesis of biologically active heterocyclic compounds using readily available, inexpensive, and environment friendly catalysts [21][22][23][24][25][26], herein we are report the synthesis of octahydro-quinazolin-2,5-diones by the one-pot multi-component reaction of aromatic aldehydes, dimedone, and urea using SiO 2 -NaHSO 4 as an efficient catalyst in water. We have found that SiO 2 -NaHSO 4 catalyzes the reaction between aromatic aldehydes, dimedone, and urea in an aqueous medium efficiently to afford the desired products in excellent yield within 1-2 h. The catalyst can be easily prepared [18] and safely handled, making the method more advantageous over other conventional methods and catalysts.…”
Section: Catalytic Performance Of Sio 2 -Nahsomentioning
confidence: 99%
“…Furthermore, SiO 2 -NaHSO 4 has been used in the protection of aldehydes with 2-mercaptoethanol [18]. In a continuation of our work into the synthesis of biologically active heterocyclic compounds using readily available, inexpensive, and environment friendly catalysts [21][22][23][24][25][26], herein we are report the synthesis of octahydro-quinazolin-2,5-diones by the one-pot multi-component reaction of aromatic aldehydes, dimedone, and urea using SiO 2 -NaHSO 4 as an efficient catalyst in water. We have found that SiO 2 -NaHSO 4 catalyzes the reaction between aromatic aldehydes, dimedone, and urea in an aqueous medium efficiently to afford the desired products in excellent yield within 1-2 h. The catalyst can be easily prepared [18] and safely handled, making the method more advantageous over other conventional methods and catalysts.…”
Section: Catalytic Performance Of Sio 2 -Nahsomentioning
confidence: 99%
“…of indole with the carbonyl groups. Various Brönsted acids, [6][7][8] Lewis acids, 9-11 heterogeneous acidic catalyst,…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of applications of benzodiazepines has attracted many researchers and various methods are known for their synthesis using different catalysts under different conditions. These methods include condensation of o-phenylenediamine and ketones in the presence of a variety of catalysts like p-toluenesulfonic acid 8 , silica sulfuric acid 9 , p-nitro benzoic acid 10 , sodium tetrachloroaurate(III) dehydrate 11 , AlCl 3 12 , polyethylene glycol 13 . But these methods involve many limitations like tedious work up procedure, producing undesired washes, applications of expensive catalyst and reagents, long reaction times, unsatisfactory yield; require separation of the catalyst from the product and formation of side products.…”
Section: Introductionmentioning
confidence: 99%